Meningkatkan Kemampuan Menulis Cerita Kembali Melalui Pemanfaatan Media Gambar Seri - Okta Mela Cikal Santoso; Rafiqa Ilma Meinina; Fufa Masruro (Hikamatzu | Journal of Multidisciplinary, 2025)
The ability to retell stories in writing is a skill that must be mastered in Indonesian learning at the elementary school. Writing is a fundamental skill that every student should possess, yet many still face difficulties in expressing ideas, organizing thoughts, and constructing coherent sentences. And also contributing factor is the lack of engaging and innovative learning media provided by teachers. This study is to improve the writing story skill of second-grade students at SDIK The Naff Kediri. The research employed Classroom Action Research (CAR) through two cycles. Data were collected with , tests, observation and documentation. The results of using serial picture media showed significant improvement in terms of grammar, story sequencing, and word choice. The use of serial picture media increased the percentage of students achieving learning mastery. Student learning mastery continuously improved, from only 38.4% in the pre-cycle post-test, increasing to 61.6% in Cycle I, and finally reaching 80.8% in Cycle II